Citrus hystrix DC. Peel Essential Oil Protects Mice from UVB-Induced Skin Damage through Antioxidant and Immunomodulatory Properties - Nhung, Tran Thi Phuong; Quoc, Le Pham Tan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
This study evaluated the protective effects of Citrus hystrix peel essential oil (EOCH) against UVB-induced skin damage in mice. The mice were randomly divided into six groups: a normal control, a UVB-exposed group, a UVB+VAP group, and three EOCH-treated groups receiving 1%, 5%, or 10% EOCH. UVB exposure was applied for 4 weeks to induce skin damage. Skin damage was assessed by scoring lesions and measuring moisture levels, while oxidative stress was evaluated by determining malondialdehyde (MDA) and hydrogen peroxide (H2O2) levels in the organs. The antioxidant defense was analyzed via the activities of glutathione peroxidase (GPx), glutathione reductase (GR), and thioredoxin reductase (TRx), along with the GSH/GSSG ratio. Immune response was assessed by measuring white blood cell (WBC) counts and evaluating phagocytic activity. UVB exposure increased skin damage scores to 3.6±0.55 and reduced moisture from 34.88±0.83% to 16.61±0.53% (p < 0.05). In contrast, the EOCH10 group restored damage scores to 0 and moisture levels to 31.85±0.34% (p < 0.05 vs. UVB). EOCH10 also significantly lowered MDA and H2O2 levels and enhanced antioxidant enzyme activities. Moreover, immune parameters were improved, with WBC counts, PR, and PI showing significant recovery (p < 0.05). Overall, EOCH demonstrated comprehensive protective effects against UVB-induced skin damage, supporting its potential as a natural therapeutic agent.